Preliminary analysis on the adoption of agile software development methodology in Indonesia - Al-Kautsar, Emyr; Salleh, Norsaremah; Hoda, Rashina; Asnawi, Ani Liza (2013)
Since the introduction of the Agile Manifesto over a decade ago, software industries around the world have started to change their software development process from traditional to Agile methods. In-depth research studies conducted in Asia Pacific countries such as India, Malaysia, and New Zealand have provided valuable insight into Agile adoption and practice in these countries. However, the state of Agile adoption in Indonesia has received little attention. Using survey method, this study investigates the adoption of Agile methods among 32 respondents from different software companies in Indonesia. It identifies the perceptions and level of awareness of software practitioners in using Agile methods. Findings from this study can be used as evidence about Agile adoption and practice in Indonesia and as a roadmap for future Agile-focused research studies.